2017
DOI: 10.1016/j.amepre.2016.11.022
|View full text |Cite
|
Sign up to set email alerts
|

Transgender Use of Cigarettes, Cigars, and E-Cigarettes in a National Study

Abstract: Introduction Tobacco use among transgender adults continues to be an area of research with few reported findings. The limited literature indicates higher cigarette use among transgender adults, compared with the general population. This national study is the first to report on cigarettes, cigars, and e-cigarettes by examining differences in transgender tobacco use independent of sexual orientation. Methods Data were collected in 2013 using a nationally cross-sectional online survey of U.S. adults (cisgender,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
105
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(114 citation statements)
references
References 17 publications
5
105
1
3
Order By: Relevance
“…Numerous studies have documented significantly higher rates of cigarette smoking among sexual minorities than their heterosexual counterparts (Dai, 2017; Emory et al, 2016; Fallin-Bennett et al, 2017; Hu et al, 2016; Johnson et al, 2016). Similar disparities have been observed for transgender individuals (Buchting et al, 2017; Smalley et al, 2016), although less data are available.…”
Section: Introductionsupporting
confidence: 59%
“…Numerous studies have documented significantly higher rates of cigarette smoking among sexual minorities than their heterosexual counterparts (Dai, 2017; Emory et al, 2016; Fallin-Bennett et al, 2017; Hu et al, 2016; Johnson et al, 2016). Similar disparities have been observed for transgender individuals (Buchting et al, 2017; Smalley et al, 2016), although less data are available.…”
Section: Introductionsupporting
confidence: 59%
“…Although the prevalence of smoking has fallen dramatically in the United States in recent decades, rates of smoking remain high among lesbian, gay, bisexual, and transgender (LGBT) individuals . More than 20% of lesbian, gay, and bisexual (LGB) adults and 35.5% of transgender adults are current smokers compared with 15.3% of heterosexual adults . These disparate smoking rates persist even though LGBT individuals are equally as interested in quitting smoking and are as aware of traditional smoking cessation methods as the general population …”
Section: Introductionmentioning
confidence: 99%
“…Given that lesbian and transgender or gender nonconforming persons already experience higher smoking prevalence and exposure to secondhand smoke compared to national averages, reduced effectiveness of GHWs in these populations could potentially lead to widened smoking-related health disparities. [1, 3, 4] Further research will be needed to examine whether the differential perceived effectiveness of GHWs among these groups is associated with poorer smoking-related outcomes, if and when GHWs are eventually implemented in the U.S. Additional research is also needed to determine ways to minimize inequalities in information processing of anti-smoking messages between lesbian and transgender or gender nonconforming persons and heterosexuals.…”
Section: Discussionmentioning
confidence: 99%
“…[3] In a national survey in 2013, Buchting and colleagues reported that compared with cisgender adults, transgender adults had between two to five times higher odds of current use of tobacco products including cigarettes (36% vs 21%), cigars (27% vs 9%), and e-cigarettes (21% vs 5%). [4]…”
Section: Introductionmentioning
confidence: 99%